Iron deficiency anemia during pregnancy and consequences related to it - Shumilina, Tetiana; Tsmur, Olga (The Ukrainian Scientific Medical Youth Journal, 2022)
the article summarizes the arguments and counterarguments in the scientific discussion on the mechanisms of iron deficiency anemia. The main purpose of this study is to summarize information on the effects of iron deficiency anemia during pregnancy and its consequences. Due to a detailed study of the literature, their systematization and approaches to solving the problem, it was found that antenatal anemia is a risk factor for maternal and perinatal mortality, premature birth, low birth weight infants and postpartum hemorrhage. Maternal anemia can also be associated with poor development of the baby's nervous system. Recent advances in systemic and placental iron homeostasis may improve therapeutic efficacy by varying the dose and frequency of oral iron intake. And intravenous iron is a safe way to quickly correct maternal anemia. The relevance of the study of this pathology is that it largely determines the perinatal and maternal morbidity. However, today there is no clear idea of ​​the features of the molecular and vascular mechanisms of iron deficiency anemia, so this leads to inconsistencies in the treatment of such pregnant women, which prevents timely, adequate treatment and prevention. The study used methods of bibliographic and content analysis of literature, semantic grouping, as well as a comparative approach and synthesis on new research on the mechanisms of iron deficiency anemia, iron homeostasis and current definitions of IDA during pregnancy, adverse effects on mother and newborn, associated with anemia, as well as the latest recommendations for the treatment of IDA during pregnancy and postpartum. The official documents found on the websites were analyzed and the relevant information was grouped and compared. The article presents the results of studies that have shown that iron plays a key role in the normal and pathological course of pregnancy and affects the development of the newborn. Iron uptake and metabolism are strictly regulated, and a full study of iron metabolism during pregnancy is of interest for preventing complications in the mother and fetus. This paper emphasizes the need for early detection of iron deficiency. In addition, it is important to treat the deficiency to ensure optimal development of the newborn. At present, measures such as oral or intravenous iron do not appear to be working to the extent necessary to achieve the WHO's goal of reducing the prevalence of anemia in women of childbearing potential by 50%. This may be due in part to uncertainty about how best to investigate, prevent, and treat maternal anemia. The development of our understanding of the physiology of iron has led to the possibility of significant improvement by changing the dosing strategy of oral iron. New laboratory iron levels, such as hepcidin, may ultimately help manage iron deficiency therapy, but a recent study found no benefit from using a hepcidin-based screening and treatment approach over the WHO recommended regimen. Therefore, further research is needed on patient-centered outcomes and cost-effectiveness. The results of the study may be useful for primary care physicians, gynecologists, therapists.